The Cards of Internal Passports of the Population of Kaunas City of the 1920–1940s as a Source of Genealogy and Local History - Balkus, Mindaugas (Bibliotheca Lituana, 2019)
This article analyzes the cards of internal passports issued in Kaunas city in 1920–1940 and the sociodemographic data of the population (nationality, confession, place of birth, work activity, etc.) provided in them. Their significance for the researches of genealogy and local history is discussed. It was found that in 1920–1940, 89 620 people received internal passports in Kaunas, including 58.76% Lithuanians, 30.27% Jews, 3.16% Poles, 3.12% Germans, 2.74% Russians, 0.33% Belarusians; 59.13% of the persons who received internal passports in Kaunas were Catholics, 28.9% – Jews, 5.44% – Evangelical Lutherans and Evangelical Reformats, 3.14% – Orthodox, 0.96% – Old Believers. These results are in many cases close to the data of the 1923 general census of the Lithuanian population; 35.22% of the residents of Kaunas were born in this city, 11.4% – in Kaunas County, 6.86% – in then-Soviet Union’s territory, while the rest – in the different regions of Lithuania and abroad. According to the character of the working activity (occupation), Lithuanians were significantly dominant among the officials (90.94%), being farmers (88.05%), servants (82.84%), or workers (75.85%), while Jews were predominant among traders (83.2%).
Keywords: Kaunas; interwar; internal passport cards; statistics; demographics; number of residents; ethnical composition; places of birth; confessional composition; occupation; genealogy; local history